Inception Report: The Development of a National Framework for Weather, Water and Climate Services for Zambia (NFWCS-ZM) - Mamadi and Company (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This inception report details the approach that will be conducted in the completion of the project, which is spread across ten work packages designed to deliver on the work objectives. The approach seeks to bring about delivery excellence to enable the full implementation of the Development of a National Framework for Weather, Water, and Climate Services (NFWCS-ZM) for Zambia.